Cortical evidence for negative search templates. Issue 1 (16th March 2017) - Reeder, Reshanne R.; Olivers, Christian N. L.; Pollmann, Stefan
ABSTRACT: A "target template", specifying target features, is thought to benefit visual search performance. Setting up a "negative template", specifying distractor features, should improve distractor inhibition and also benefit target detection. In the current fMRI study, subjects were required to search for a target among distractors enclosed in coloured circles. Before search, one of three colour cues appeared: a positive cue indicating the target will appear in the same colour, a negative cue indicating only distractors will appear in the same colour, or a neutral cue indicating that the same colour will not appear in the search display. fMRI results revealed down-regulation of neural processing in large parts of visual cortex following negative compared to positive cues. We further found a general attention inhibition mechanism in SPL/precuneus for neutral cues compared to positive and negative cues. These results suggest a cortical distinction between target templates, negative templates, and task-irrelevant distractor inhibition.